Sarcoidosis misdiagnosed as pulmonary malignancy: a case report - Zhang, Houlu; Huang, Yubin; Zhao, Xiuyi; Fan, Daming; Xing, Zhongxiang; Sun, Xiaoming; Zhu, Liangming (Frontiers in Oncology, 2026)
Sarcoidosis is an idiopathic multisystem disease characterized by non-caseating granulomas primarily composed of epithelioid macrophages. The lungs and lymph nodes are the most commonly affected organs. Clinical manifestations of sarcoidosis vary widely, and its radiographic features often overlap with those of malignant tumors, especially pulmonary malignancy, increasing the diagnostic challenge. This article presents a case of sarcoidosis misdiagnosed as pulmonary metastatic in a patient with a history of pulmonary malignancy. Nine months after surgery for left lung adenocarcinoma, the patient had a follow-up that revealed elevated CEA levels (14.98 ng/ml). ¹8F-fluorodeoxyglucose positron emission tomography/computed tomography (¹8F-FDG PET/CT) revealed 18F-fluorodeoxyglucose (¹8F-FDG) metabolic hot spots in the right upper lung lobe, bilateral pleura, and spleen, as well as metabolically active lymph nodes in several locations, including the mediastinum, hilum, hepatic hilum, omental bursa, and retroperitoneum. The largest lymph node, located in the mediastinum, had a maximum standardized uptake value (SUV max) of 21.5, indicating intense glucose metabolism and suggesting pulmonary malignancy recurrence with metastasis to the pleura and spleen. To clarify the diagnosis, we conducted a lymph node biopsy and histological examination, which ultimately confirmed sarcoidosis. This case highlights that, in patients with pulmonary malignancy, sarcoidosis can coexist with or occur alternately alongside malignancy, and the imaging features of both conditions lack specificity, potentially leading to misdiagnosis. These observations underscore that reliance on imaging alone is insufficient for differential diagnosis, and that other diagnostic methods, particularly histopathological evidence, should be integrated to achieve a comprehensive assessment.